Memahami Pengaruh Lingkungan Sekolah terhadap Kemampuan Membaca Lancar Level 3 pada Anak Sekolah Dasar - Rizki, Dwi; Putri, Siti Gahara; Chandra, Chandra; Wijanarko, Tiok (Lembaga Yasin AlSys, 2024)
This research aims to understand the influence of the school environment on the reading fluency of fifth-grade elementary school students. The school environment includes factors such as the quality of teaching, the availability of reading materials, support from teachers, and a conducive learning atmosphere. The research methods used are surveys and observations in elementary schools. The results of the study show that a good and supportive school environment has a positive correlation with students' reading fluency. Factors such as interactive teaching approaches, adequate library availability, and emotional support from teachers have been proven to improve students' reading abilities. These findings underline the importance of creating a conducive school environment for the development of literacy in elementary students.